KAEDAH MENGALAMI-MENGHAYATI DALAM PENGAJARAN BAHASA IBAN DENGAN MENGGUNAKAN ENSERA: EXPERIENCE-IMMERSED METHOD USING ‘ENSERA’ IN IBAN LANGUAGE TEACHING - Anak Gerry, Doratya; Anak Osup, Chemaline (Jurnal Pengajian Melayu (JOMAS), 2020)
This study was conducted to identify methods and techniques employed by teachers when they teach the Iban language using ‘ensera’ or folk tales. ‘Ensera’ refers to traditional Iban folklore about heroes from the mystical world of Panggau Libau that is shared through ‘kanaka’ (songs) interspersed with explanation and conversation in the form of prose. The research design utilised the qualitative approach by executing fieldwork involving 10 teachers at SMK Engkilili, Lubok Antu, Sarawak. Data was collected using a semi-structured interview and a checklist. The constructivist and moral theories were employed to analyse the methods and techniques as well as assess the teachers’ mastery of the ‘ensera’. Results were obtained by analysing interview transcripts. Findings revealed that the technique of ‘mengalami-menghayati’ (experience-immersed) was one of the best practices in the context of teaching using ‘ensera’. The teaching techniques used were identified through various classroom activities such as reading, storytelling and acting. Teaching Iban language using ‘ensera’ might also promote values such as courage, humanity, goodwill, diligence, patience and generosity. Therefore, the technique of ‘mengalami-menghayati’ should be made routine by Iban language teachers. Consequently, students might be able to express themselves well as a result of the knowledge, opinion, experience, enjoyment and appreciation derived from the learning of the Iban language through ‘ensera’. Keyword: Experience-immersed method, teaching technique, value of ensera.